Assessment of vitality Berberis thunbergii DC. in Kyiv: Photosynthesis and Phytopathology - Strashok, Oleksandra; Ziemiańska, Monika; Kolesnichenko, Olena; Salnikova, Anna; Oleg, Kytaev (Journal of Phytology, 2022)
The process of functioning of the photosynthetic apparatus is one of the most vulnerable to stress factors. The information about the functional state of plants and the prospects for their use in urban greening can provide methods of fluorescence analysis. The objective of this research was to develop the state of plants Berberis thunbergii DC. which grow in the Mariinskyi Park (Kyiv) by the content of photosynthetic pigments and fluorescence induction chlorophyll (FIC). The article presents the results of the evaluation of fluorescence induction (FI) indicators and the content of photosynthetic pigments B. thunbergii according to the degree of damage by powdery mildew. Experimental plants were planted in the chernozem layer of 50 cm (humus content 4 %). The plants grow in a group planting of Picea glauca ‘Conica’ and Chlorophytum comosum ‘Variegatum’ directly 1.5–5 m from the highway under the canopy of Tilia cordata Mill. Moreover, the variability of FI curves in the absence/presence of plant lesions. The authors investigated the relationship between the content of photosynthetic pigments and FI. The degree of damage to experimental plants by powdery mildew affects the total chlorophyll content (a+b) and decreases by approximately 16 %, 7 %, and 5 % compared to the control. Recorded gradually disappear FI curves in plants with the highest degree of damage which affect photochemical reactions due to the slowing down of the outflow of Calvin cycle enzymes.